2021
DOI: 10.11591/ijece.v11i1.pp536-544
|View full text |Cite
|
Sign up to set email alerts
|

Secured node detection technique based on artificial neural network for wireless sensor network

Abstract: The wireless sensor network is becoming the most popular network in the last recent years as it can measure the environmental conditions and send them to process purposes. Many vital challenges face the deployment of WSNs such as energy consumption and security issues. Various attacks could be subjects against WSNs and cause damage either in the stability of communication or in the destruction of the sensitive data. Thus, the demands of intrusion detection-based energy-efficient techniques rise dramatically as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Artificial neural networks (ANN) is one of many important features of artificial intellegent [25,26]. The neuron is the basic element of an artificial neural network which has a summer and an activation function [26] as shown in Figure 3 The model of a neuron is given by: For ensure best result and fast convergence it must to use the algorithm equation [27]. The main algorithm equations of the neural network as ( 13), (14).…”
Section: Neural Network Principlementioning
confidence: 99%
“…Artificial neural networks (ANN) is one of many important features of artificial intellegent [25,26]. The neuron is the basic element of an artificial neural network which has a summer and an activation function [26] as shown in Figure 3 The model of a neuron is given by: For ensure best result and fast convergence it must to use the algorithm equation [27]. The main algorithm equations of the neural network as ( 13), (14).…”
Section: Neural Network Principlementioning
confidence: 99%
“…) 𝐸 𝐷𝐴 + 𝐸 𝑇𝑥𝐶𝐻𝐴 (10) where (𝐸 𝑅𝑥𝐶𝐻𝐴 = 𝑙 𝑚 𝐸 𝑒𝑙𝑒𝑐 ) is the dissipating energy to receive the lm-bits message from the active cluster member nodes. During the aggregation of data from active CM nodes, the energy dissipated to aggregate data 𝐸 𝐷𝐴 can be expressed as ( 𝐸 𝐷𝐴 = 𝑙 𝑚 𝐸 𝑑𝑎 ).…”
Section: − Energy Consumption Analysis For Clustering Functionmentioning
confidence: 99%
“…where W is the stress concentration factor; B is the buried depth of coal seam, n; and x is the bulk density of the overlying strata, WB/n. In the above formula, assuming that the internal friction angle θ [23] is a fixed value, it is concluded that y 1 only increases with the increase of the thickness of the coal seam under the same coal seam condition. erefore, the peak point of the support pressure in front of the working face [24] increases with the height of the mining.…”
Section: Calculation Of Bearing Pressurementioning
confidence: 99%